Electronic origin of the anomalous melting of sodium under pressure - Yuan Liu; Hanyu Liu; John S. Tse (Proceedings of the National Academy of Sciences, 2025)
Despite extensive experimental and theoretical investigations, the fundamental electronic origin of compressed sodium’s melting temperature reversal under pressure, characterized by a maximum and a minimum in its melting curve, remains unclear. A recent two-state model proposed for high-pressure potassium, which exhibits a similar melting anomaly, attributes this behavior to changes in the distribution of non-nuclear localized electrons (electrides), resulting in distinct liquid phases. To test this hypothesis for sodium, we conducted ab initio molecular dynamics simulations to examine its atomic dynamics and electronic properties under high pressure. Our results reveal no discontinuities in atomic or electronic transport properties, nor any evidence of multiple inherent structural forms. Furthermore, the electronic screening potential governing liquid structure remains largely unchanged above 50 GPa. Instead, we find that the key parameter responsible for the melting anomaly arises from differences in the average number of electrons per non-nuclear maximum, which affects the relative packing densities of the liquid and solid phases.